MOTIVASI BELAJAR IPA PADA PEMBELAJARAN E-LEARNING CLASS DI KELAS VII SMPN 45 PEKANBARU PADA MASA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the students' motivation to learn science in e-learning classes in class VII SMPN 45 Pekanbaru during the covid-19 pandemic. This research was conducted in November 2021 at SMPN 45 Pekanbaru. This research is a descriptive research with a quantitative approach. Due to the covid-19 pandemic, research data was collected through a google form by asking students to give their responses to motivational questionnaire statements. Based on the results of research on science learning motivation in e-learning classes in class VII SMPN 45 Pekanbaru during the covid-19 pandemic, it describes high learning motivation with a percentage of 75.98%.Key Words: Motivation, E-Learning Class, Covid-19.